RUNNING EVENT “TRACKPRESSO: 5K COLOR RUN 2024 DI KOTA SEMARANG, JAWA TENGAH” SEBAGAI PROGRAM MANAGER, PRODUCTION, PIC EVENT, SERTA LIAISON OFFICER DI DALAM RANGKAIAN ACARA - Gracella Rosaline, Maria; Manalu, S. Rouli (Interaksi Online, 2024)
This field project discusses the entire preparation and execution of the Trackpresso: 5K Color Run 2024 event. Anak Panah Kopi, as the client, collaborated with the project team, motivated by the desire to create an event that has been trending in recent months, using the 'riding the wave' strategy as the basis for conducting this project. This report utilizes Integrated Marketing Communication as the conceptual framework, applying eight tools, and event management principles as outlined in Joe Goldblatt's book "Special Events" which explains the execution of events through five stages, from research to evaluation. The Trackpresso: 5K Color Run targeted an audience of 150 participants and was held on August 24th in Semarang. The results of this report show that the event was successfully executed according to the initial target, with 150 participants joining the Trackpresso: 5K Color Run. As the Program Manager, the main person responsible for the project, I successfully managed the project and the entire team, effectively utilizing resources to ensure the smooth execution of the event. Additionally, in the roles of Production Lead, Event PIC, and Liaison Officer, I achieved the predetermined targets: overseeing procurement, designing and organizing an e-sports competition, and negotiating with event performers and other collaborators. Therefore, this report recommends that the Trackpresso: 5K Color Run project can provide academic contributions to the preparation of similar events in the future.